Silicon, by modulating homeostasis and nutritional efficiency, increases the antioxidant action and tolerance of bell peppers to phosphorus deficiency - Costa, Milton Garcia [UNESP]; da Silva, Bianca Cavalcante [UNESP]; Alves, Deyvielen Maria Ramos [UNESP]; de Lima, Paulo Sergio Rodrigues [UNESP]; Prado, Renato de Mello [UNESP] (Elsevier, 2025)
The effects of phosphorus deficiency on bell pepper cultivation and the role of silicon in mitigating this deficiency warrant further investigation. The use of silicon could be a promising sustainable alternative to increase the tolerance of this vegetable to P-deficient environments, which is a worldwide issue, but the mechanisms involved need to be elucidated. To this end, this research aimed to investigate the impact of Si on mitigating P deficiency in bell pepper plants, exploring its effects on nutritional homeostasis and physiological parameters under conditions of P sufficiency and deficiency. This study was conducted under controlled conditions with two P conditions (deficiency and sufficiency) combined with two Si conditions (0.0 and 2.0 mM) arranged in a completely randomized design with five repetitions. We found that P deficiency damage in bell pepper plants compromised the nutritional efficiencies of P and N, photochemical efficiency, total soluble sugar production, and growth, but the adaptive response of the plant to mitigate these damages induced non-enzymatic antioxidant defense mechanisms and favored homeostasis by increasing the C/N, C/P, and N/P ratios. This occurred because Si favored stoichiometric homeostasis of C/N, C/P, and N/P in the plant while simultaneously reducing stress with substantial increases in the production of antioxidant compounds, such as ascorbic acid, phenolic compounds, anthocyanin, carotenoids, and photosynthetic pigments, enhancing photochemical efficiency and C use, and consequently, plant growth. This study offers a sustainable option for addressing P deficiency using Si, strengthening large-scale horticulture, given the common occurrence of P-limited growing environments.
Keywords: Beneficial element; Capsicum annuum L.; Nutritional homeostasis; Nutritional stress; Vegetable nutrition